Positron emission tomography (15O-water, 11C-acetate, 11C-HED) risk markers and nonsustained ventricular tachycardia in hypertrophic cardiomyopathy - Peter Magnusson; Jonny Nordström; Hendrik J. Harms; Mark Lubberink; Fredrik Gadler; Jens Sörensen; Stellan Mörner (International Journal of Cardiology: Heart & Vasculature, 2020)
Background: The objectives of the study were to describe positron emission tomography (PET) parameters, using the tracers 15O-water at rest/stress, 11C-acetate, and 11C-HED, with regard to nonsustained ventricular tachycardia (NSVT) in hypertrophic cardiomyopathy (HCM). PET offers quantitative assessment of pathophysiology throughout the left ventricular segments, including the endocardium/epicardium. The potential use PET in risk stratification remains to be elucidated. NSVT provides a marker for sudden cardiac death. Methods: Patients with a validated diagnosis of HCM who had an implantable cardioverter-defibrillator were interrogated at 12 months and independently of PET-examinations. Results: In total, 25 patients (mean age 56.8 ± 12.9 years, 76% males) were included and 10 reported NSVT. Mean myocardial blood flow (MBF) at rest was 0.91 ml/g/min and decreased at stress, 1.59 ml/g/min. The mean gradient (endocardium/epicardium quotient) at rest was 1.14 ± 0.09, while inverse at stress (mean 0.92 ± 0.16). Notably, MBF gradient at stress was significantly lower in patients with NSVT (p = 0.022) and borderline at rest (p = 0.059) while global MBF at rest and stress were not. Mean myocardial oxygen consumption (MVO2) was 0.088 ml/g/min (higher in NSVT, p = 0.023) and myocardial external efficiency 18.5%. Using 11C-HED, the mean retention index was 0.11 min−1 and a higher volume of distribution (p = 0.089) or transmural gradient of clearance rate (p = 0.061) or lower clearance rate (p = 0.052) showed a tendency of association of NSVT. Conclusions: The endocardium/epicardium MBF gradient at stress is significantly lower in HCM patients with NSVT. This provides a novel approach to further refine risk stratification of sudden cardiac death. Keywords: Arrhythmia, Hypertrophic cardiomyopathy, Positron emission tomography